MODERNIZATION OF BALINESE CULTURE: A CRITICAL DISCOURSE ANALYSIS OF TEUN A VAN DIJK YOUTUBE KISARASA - Khotimah, Khusnul; Hariyanti, Nunik (Universitas Muhammadiyah Jakarta, 2024)
Abstract Modernization is a global phenomenon that affects cultures, including Bali. This research will explore the Balinese cultural modernization phenomenon. This research aims to analyze the impact of modernization on Balinese culture by using the critical discourse approach developed by Teun A. Van Dijk. The main focus of this research is Kisarasa's YouTube content, which becomes a place to explore the changes and adaptations of Balinese culture. This research method uses a qualitative approach through data collection techniques of literature study, video analysis, and documentation. The literature study was conducted to collect information on Koentjaraningrat's seven elements of culture. Video analysis was conducted to explore how Balinese cultural elements are presented and the changes due to modernization. Documentation was done by providing video clips that had been identified as relevant to Balinese culture and by the predetermined criteria. The data was analyzed using the content analysis method with a critical discourse approach, through three components of analysis, namely, text, social cognition, and social analysis. To ensure data validity, a source triangulation technique was applied by comparing data from the three collection methods. The result is YouTube Kisarasa suggests that modernization is driving the adaptation of Balinese culture, which maintains traditional core values but is not separated from modern lifestyles. This research contribute to the understanding of the modernization of Balinese culture and how critical discourse analysis and cultural studies can complement each other to provide a deeper insight into social and cultural change in a modern context.